POTENSI PERAN FARMASIS DALAM MENINGKATKAN KUALITAS HIDUP PASIEN LANJUT USIA: PERSPEKTIF RAWAT RUMAH - Dyah Aryani Perwitasari; Arief Muttaqien (Universitas Ahmad Dahlan, 2012)
The Home Health Care program is getting popular as well. One of the outcome measured in this program is patient's quality of life. Home Health Care program is a multidisciplin program, which need the pharmacist role. The aim of this study was to find out the potencial pharmacist role in increasing elderly patients'quality of life participated in Home Health Care program. This study used descriptive design with prospective data sampling. (World Health Organization Quality of Life) We used WHOQoL as the instrument. The study period was conducted for 13 week in 2009 by visiting the patients at their homes. The patients were participated in Home Health Care program of Dr Sardjito hospital, Yogyakarta. Data was descriptively analized. We're recruited seven subjects in this study. In average, their quality of life was low (46,1±4,4). All of the patients received polypharmacy and were found the patients incompliance in taking the medicines. The role of pharmacist were important in Home Health Care program for elderly patients to increase their quality of life. The pharmacists are supposed to do the drug used monitoring, especially to the elderly patients with polypharmacy. The advance technique for communication, information, and education is suggested to the pharmacist in this program.